ASSISTÊNCIA PSICOLÓGICA À IDOSOS EM INSTITUIÇÃO DE LONGA PERMANÊNCIA - Drügg, Angela M. S.; Gai, Gabriela N.; Comerlato, Carla F.; Nascimento, Karoline d. M.; Aires, Juliana F.; Santos, Maria A. N. d.; Padilha, Alessandra S. (Salão do Conhecimento, 2013)
Resumo